The Effect of Reward, Career Development and Task-Oriented Leadership Style on Employee Performance with Job Satisfaction as Intervening Variables - Maria Ade Irma Kue; Nuryakin Nuryakin; Arni Suwanti (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
The Increasingly fierce competition requires every party in the business world to always be responsive to changes that occur. To respond to this competition requires companies including hospitals to make various improvements in all aspects including in the field of human resources in addition to other resources such as capital and technology. This research was conducted to determine the effect of reward, career development and task-oriented leadership style on employee performance with job satisfaction as an intervention variable. The research design is descriptive quantitative and purposive sampling. Causality analysis with the SEM-Partial Least Square model to test the hypothesis of the effect of reward, career development, and task-oriented leadership style on employee performance and the role of job satisfaction as an intervention variable. The result of this research is reward and leadership style has a positive and significant effect on job satisfaction and employee performance. Job satisfaction mediates the influence between reward and task-oriented leadership style. Career development has not positive and significant effect on job satisfaction and job satisfaction does not mediate the effect of career development on performance.Abstrak: Kompetisi yang semakin ketat menuntut setiap pihak di dunia bisnis untuk selalu tanggap terhadap perubahan yang terjadi. Untuk merespons persaingan tersebut menuntut pihak perusahaan termasuk rumah sakit melakukan berbagai peningkatan di segala aspek termasuk dalam bidang sumber daya manusia di samping sumber daya yang lain seperti modal dan teknologi. Penelitian ini dilakukan untuk mengetahui pengaruh reward, pengembangan karir dan gaya kepemimpinan berorientasi pada tugas terhadap kinerja karyawan dengan kepuasan kerja sebagai variabel intervening. Design penelitian ini merupakan deskriptif kuantitatif dan purposive sampling. Analisis kausalitas dengan model SEM-Partial Least Square untuk menguji hipotesis pengaruh reward, pengembangan karir, dan gaya kepemimpinan berorientasi tugas terhadap kinerja pegawai dan peran kepuasaan kerja sebagai variabel intervening. Hasil penelitian adalah reward dan gaya kepemimpinan berorientasi pada tugas berpengaruh positif dan signifikan terhadap kepuasan kerja dan kinerja pegawai. Kepuasan kerja memediasi efek antara reward dan gaya kepemimpinan berorientasi tugas. Pengembangan karir tidak berpengaruh positif dan signifikan terhadap kepuasan kerja dan kepuasan kerja tidak memediasi pengaruh pengembangan karir terhadap kinerja.